Age, Diet and Epidermal Signaling Modulate Dermal Fibroblasts’ Adipogenic Potential - Walendzik, Katarzyna (Int J Mol Sci, 2020)
The recognition of a distinct fat depot, the dermal white adipose tissue (dWAT), points out the complexity of the interaction among skin resident cells: keratinocytes, dermal fibroblasts (DFs) and adipocytes in response to physiological (diet, age) and pathological (injury) stimulations. dWAT has been recognized as a significant contributor to thermoregulation, hair cycle, immune response, wound healing and scarring. In this study, we examined age- and diet-related changes in dWAT modulation and DFs’ adipogenic potential. The data showed that diet modulates dWAT expansion predominantly by hypertrophy, whereas age affects the pool of adipocyte progenitor cells in the skin indicating its role in dWAT hyperplasia. Analysis of DFs’ migratory abilities in the model of skin explants isolated from the skin of young, old, low (LFD)- or high (HFD)-fat diet C56BL/6 mice revealed that HFD, regardless of animal age has the most profound stimulatory impact of DF migration. We determined that the adipogenic potential of DFs is comparable to stromal vascular fraction (SVF) of inguinal fat depot and ear mesenchymal stem cells (EMSC). We also showed the stimulatory role of epidermally expressed transcription factor Foxn1 on adipogenic signaling: bone morphogenetic protein 2 (Bmp2) and insulin-like growth factor 2 (Igf2) in keratinocytes.